PENGARUH BEBAN KERJA ADMINISTRATIF PENGISIAN LAPKIN DAN KEPEMIMPINAN KEPALA SEKOLAH MELALUI MOTIVASI KERJA TERHADAP KINERJA GURU PPPK SMP DI KECAMATAN SEBERANG ULU 2 PALEMBANG - Rachmat Shafrullah; Suwito Eko Pramono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the effect of LAPKIN administrative workload and principal leadership on the performance of PPPK junior high school teachers, both directly and indirectly through work motivation as a mediating variable. This research employed a quantitative approach involving 83 PPPK teachers from junior high schools in Seberang Ulu II District, Palembang, selected using total sampling. Data were collected through validated and reliable questionnaires and analyzed using path analysis, multiple regression, and Sobel test. The findings showed that LAPKIN administrative workload had no significant effect on teacher performance or work motivation. In contrast, principal leadership had a positive and significant effect on both teacher performance and work motivation. Work motivation also significantly influenced teacher performance. Furthermore, work motivation was unable to mediate the relationship between LAPKIN administrative workload and teacher performance. However, work motivation successfully mediated the relationship between principal leadership and teacher performance. These findings indicate that participative principal leadership plays an important role in improving teachers’ motivation and performance. Therefore, school principals are encouraged to strengthen leadership practices that support teacher productivity and effectiveness.